Extreme resistance to late blight disease by transferring 3 R genes from wild relatives into African farmer-preferred potato varieties. - Webi, E.N.; Kariuki, D.; Kinyua, J.; Njoroge, A.W.; Ghislain, M.; Magembe, E. (Academic Journals, 2019)
Three late blight resistance (R) genes from wild potato species were transferred as a stack into the farmer-preferred varieties ‘Tigoni’ and ‘Shangi’. Transgenic events were tested by detached-leaf assays (DLA) and whole-plant assays (WPA) with isolates of Phytophthora infestans using 20,000 sporangia / mL inoculum. For the first DLA, 9 out of 13 ‘Tigoni’ and 10 out of 12 ‘Shangi’ transgenic events had scores below 3% of leaf affected area. 17 of the 19 transgenic events with low scores were subjected to a second DLA using two different P. infestans isolates. 8 of them exhibited extreme LB resistance while the remaining 9 transgenic events showed hypersensitive response (HR). 6 transgenic events (2 ‘Tigoni’ and 4 ‘Shangi’) with extreme resistance by DLA were subjected to WPA and they all exhibited extreme resistance to LB. Hence, this study demonstrates that a simple DLA predicts high level of resistance to late blight. R gene expression analysis in 18 transgenic events showed different transgenic events exhibiting different levels of expression in the three genes. However, that pathogen induction and / or high R gene expression are necessary for extreme resistance when transgenic events bear a stack of three R genes was not observed.